2023
DOI: 10.1186/s40634-023-00603-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular activity of the lower‐extremities during running, landing and changing‐of‐direction movements in individuals with anterior cruciate ligament reconstruction: a review of electromyographic studies

Abstract: Purpose Running, jumping/landing and cutting/change of direction (CoD) are critical components of return to sport (RTS) following anterior cruciate ligament reconstruction (ACLR), however the electromyographic (EMG) activity patterns of the operated leg during the execution of these tasks are not clear. Methods A systematic review was conducted to retrieve EMG studies during running, jumping/landing and cutting/(CoD) in ACLR patients. MEDLINE, PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 159 publications
0
6
0
Order By: Relevance
“…Reduced muscle activity after RTS has been associated with poor performance and reduced dynamic stability of the knee during landing, 33 underscoring the clinical significance of understanding changes in muscle activity at RTS. 20,34 On the other hand, previous studies have reported earlier onset times or longer durations of muscle activities in the quadriceps and hamstring muscles before landing, 35 indicating increased pre-muscle activity as a protective mechanism to stiffen the joint in preparation for impact after landing. 36 However, these findings were mainly observed during the initial rehabilitation period (4 to 6 months post-surgery), whereas this study and others included subjects approximately 15 months 32 and 60 months 33 post-surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Reduced muscle activity after RTS has been associated with poor performance and reduced dynamic stability of the knee during landing, 33 underscoring the clinical significance of understanding changes in muscle activity at RTS. 20,34 On the other hand, previous studies have reported earlier onset times or longer durations of muscle activities in the quadriceps and hamstring muscles before landing, 35 indicating increased pre-muscle activity as a protective mechanism to stiffen the joint in preparation for impact after landing. 36 However, these findings were mainly observed during the initial rehabilitation period (4 to 6 months post-surgery), whereas this study and others included subjects approximately 15 months 32 and 60 months 33 post-surgery.…”
Section: Discussionmentioning
confidence: 98%
“…We should consider that the prevalence of recurrent ACL rupture is high, and ranges from 1 to 11% 2 . Additionally, the prevalence of secondary contralateral ACL injury is as high as 1 in 4 3 , which suggests an elevated risk of ACL injury among athletes who have undergone a, ACLR 4 – 6 . Even with a significant volume of research underscoring the significance of consistent evaluation of quadriceps strength following ACLR, nearly half of clinicians persist in relying solely on the duration since surgery as the primary factor to determine an individual's readiness to resume sports activities after ACLR 65 .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of recurrent ACL rupture is high, and ranges from 1 to 11% 2 . Additionally, the prevalence of secondary contralateral ACL injury is as high as 1 in 4 3 , which suggests an elevated risk of ACL injury among athletes who have undergone a, ACLR 4 – 6 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations